The implications of the interdependent configuration between trainees and supervising teachers in the supervised curriculum internship in Physical Education - Arestides Pereira da Silva Júnior; Camila Rinaldi Bisconsini; Patric Paludett Flores; Ana Luíza Barbosa Anversa; Amauri Aparecido Bássoli de Oliveira (Motrivivência, 2019)
Based on Norbert Elias' s framework, the research had the objective of analyzing the implications of the configuration between trainees and supervising teachers in the Supervised Curricular Internship in the training of Physical Education teachers. A total of 90 academics from the Physical Education (undergraduate) course and 63 trainee supervisors participated in the study. As instruments were used a questionnaire and the analysis of documents. Quantitative data were presented using descriptive statistics (%). The qualitative data were treated through content analysis and organized in the NVivo 10 software. It was verified that the analyzed indicators present a configuration of interdependence and possible implications in the accomplishment of the Supervised Curricular Internship in the initial formation in Physical Education, since the experience of the teacher, his or her qualification and professional status may favor or limit the relations established between those involved during this formative moment.